2007
DOI: 10.1038/sj.jid.5700728
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Stimulates Fibroblast Growth Factor-7 Gene Expression Via Adenosine A2b Receptor Signaling in Dermal Papilla Cells

Abstract: It has been previously reported that an adenosine receptor-mediated signal-transduction pathway in the dermal papilla cells (DPCs) of hair contributes to minoxidil-induced hair growth. In this study, we investigated this hypothesis further and have elucidated some underlying mechanisms. We performed DNA microarray analyses of DPCs and found that adenosine stimulation increases fibroblast growth factor-7 (FGF-7) gene expression levels by greater than 2-fold. Elevations of the extracellular FGF-7 protein levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 30 publications
2
63
0
Order By: Relevance
“…It stimulates VEGF production through activation of cell surface adenosine receptors, and this adenosine-mediated signal transduction pathway contributes to minoxidil-induced hair growth (9). Gene expression of FGF-7 was up-regulated by adenosine treatment in DP cells (10). Oura et al (17) demonstrated that adenosine significantly increased the anagen hair growth rate and the thickness of hair in a human clinical study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It stimulates VEGF production through activation of cell surface adenosine receptors, and this adenosine-mediated signal transduction pathway contributes to minoxidil-induced hair growth (9). Gene expression of FGF-7 was up-regulated by adenosine treatment in DP cells (10). Oura et al (17) demonstrated that adenosine significantly increased the anagen hair growth rate and the thickness of hair in a human clinical study.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (9) proposed an adenosine mediated mechanism for minoxidil-induced vascular endothelial growth factor (VEGF) production by the signaling pathway. Iino et al (10) reported that adenosine stimulates FGF-7 gene expression. However, the potential effects of adenosine on hair growth have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Among these FGF genes, FGF-7 was found to be expressed in the hair follicle. FGF-7 RNA is localized to the dermal papilla during anagen, but expression is down-regulated by the lateanagen VI stage [22]. Besides, no FGF-7 RNA was detected in follicles during catagen or telogen [23].…”
Section: Real-time Pcr (Qpcr)mentioning
confidence: 94%
“…Studies performed by the Shiseido Research Group indicate that adenosine, via A 2B AR, might stimulate hair growth through fibroblast growth factor-7 gene expression upregulation in dermal papilla cells [57].…”
Section: Therapeutic Potential Of a 2b Adenosine Receptor Agonistsmentioning
confidence: 99%